2016
DOI: 10.1002/dmrr.2814
|View full text |Cite
|
Sign up to set email alerts
|

Reduced peripheral blood mtDNA content is associated with impaired glucose‐stimulated islet β cell function in a Chinese population with different degrees of glucose tolerance

Abstract: AimsOur aim is to explore the associations between mitochondrial DNA (mtDNA) content and basal plasma glucose, plasma glucose after oral glucose administration and oxidative stress in a Chinese population with different levels of glucose tolerance. We also aimed to investigate the effect of mtDNA content on basal and oral glucose‐stimulated insulin secretion.MethodsFive hundred and fifty‐six Chinese subjects underwent a 75‐g, 2‐h oral glucose tolerance test. Subjects with diabetes (n = 159), pre‐diabetes (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…These results indicate that the mtDNA-CN has a huge potential as a biomarker of future diabetes. We also found in the two-group comparison tests that 1-h glucose had the highest significance of the glucose metabolism-related variables, which is consistent with previous findings 16 . In univariate analysis, some variables maintained their significance throughout the follow-up, while the significance of others varied according to the follow-up time.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that the mtDNA-CN has a huge potential as a biomarker of future diabetes. We also found in the two-group comparison tests that 1-h glucose had the highest significance of the glucose metabolism-related variables, which is consistent with previous findings 16 . In univariate analysis, some variables maintained their significance throughout the follow-up, while the significance of others varied according to the follow-up time.…”
Section: Discussionsupporting
confidence: 92%
“…In support of this notion, previous studies have indicated that diabetic patients with DN have higher oxidative stress than non-diabetic individuals (36,37). Furthermore, a study by Zhou et al (38) reported that reduced peripheral blood mtDNA-CN as a result of hyperglycemia-induced oxidative stress is closely associated with glucose-stimulated insulin secretion in diabetic patients. In recent years, activation of the immune system and chronic inflammation have been proposed as novel pathways involved in DN.…”
Section: Discussionmentioning
confidence: 80%
“…The characteristic of study subjects is shown in Table 1. The median (min-max) age of the study subjects was 20 (19)(20)(21)(22)(23)(24) years while mtDNA copy number was 9.56 (8.07-12.34). The correlation between mtDNA copy number with other variables is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Several diseases have been linked to mitochondrial dysfunction shown by the change of mtDNA copy number [19]. It has been reported that reduced mtDNA copy number is associated with various conditions such as visceral adiposity [11], impaired glucosestimulated islet β cell function [20], diabetic nephropathy [12], chronic kidney disease [13], Parkinson's disease [14], and prostate cancer [15]. Instead, various mixed results have been reported.…”
Section: Discussionmentioning
confidence: 99%